“Monitoreo d ella deforestacion, empleando imágenes satelitales (landsat 5 y 7), en las provincias de mariscal cáceres y tocache, Región San Martín-Perú” - Rabanal Rosillo, Hamilton (2009)
The present work was carried out in the provinces of Mariscal Cáceres and Tocache, whose surfaces are 1' 446 928 and 611 540 hectares, equivalent to 28.69 and 12.13% of the territory of the Region, respectively. Both provinces cover an area of 2' 068 468 hectares, equivalent to the 40.82% of the regional territory. The analysis covered a period of 12 years and used satellite imagery, Landsat 5 and 7 (years 1 987 and 1 999), previously corrected geometrically. For the identification and description of the units, the analysis of the images was optical (format digital) directly in the screen of the monitor and visual with support of images in format analog (paper). Field verification was carried out by land, applying brief surveys to farmers, corroborating, acquitting, describing and evaluating patterns and coverage. The results obtained are presented in different thematic maps of vegetation cover and patterns of use of land, deforestation p...